Prevalence and short‐term changes of cognitive dysfunction in young ischaemic stroke patients. (9th January 2019) - Pinter, D.; Enzinger, C.; Gattringer, T.; Eppinger, S.; Niederkorn, K.; Horner, S.; Fandler, S.; Kneihsl, M.; Krenn, K.; Bachmaier, G.; Fazekas, F.
Abstract : Background and purpose: Information on the prevalence and course of post‐stroke cognitive impairment in young stroke patients is limited. The aim was to assess a consecutive sample of acute young ischaemic stroke patients (18–55 years) for the presence and development of neuropsychological deficits. Methods: Patients prospectively underwent a comprehensive clinical and cognitive assessment, examining general cognitive function, processing speed, attention, flexibility/executive function and word fluency within the first 3 weeks after hospital admission (median assessment at day 6) and at a 3 months' follow‐up (FU). Cognitive dysfunction was defined in comparison to age‐standardized published norms. Results: At baseline ( N  = 114), deficits were highly prevalent in processing speed (56.0%), flexibility/executive function (49.5%), attention (46.4%) and general cognitive function (42.1%). These frequencies were comparable for those with FU assessment ( N  = 87). In most domains, cognitive performance improved within 3 months, except for word fluency. However, in about one‐third of patients, cognitive deficits (as defined by 1.5 standard deviations below the standardized mean) were still present 3 months after stroke. At FU, 44.0% were impaired in the domain flexibility/executive function, 35.0% in processing speed and 30.0% in attention. Conclusions: The high prevalence of cognitive deficits in acute young patients with ischaemic stroke highlights the importance of early post‐stroke cognitive assessment to capture a patient's dysfunction in a comprehensive manner and to offer adequate rehabilitation. The role of factors which promote neuropsychological deficits needs further exploration.